Photodynamic therapy of leukoplakia of the oral mucosa: experience of using method in 223 patients - T. P. Artsemyeva; D. A. Tzerkovsky (Biomedical Photonics, 2024)
The aim of this study was to analyze the immediate and long-term results of using photodynamic therapy (PDT) in patients with leukoplakia of the oral mucosa. The retrospective study included 223 patients with morphologically verified leukoplakia of the oral mucosa. Patients received treatment at the hyperthermia and photodynamic therapy department from 2013 to 2023. The average age was 51.9±8.9 years. Clinically, 211 patients (94.6%) had a flat form of the disease, 12 patients (5.4%) had a verrucous form. The photosensitizer (PS), based on chlorin e6, was administered intravenously once in doses of 1.7 to 2.5 mg/kg body weight. Irradiation of pathologically changed lesions was carried out 2-2.5 hours after the end of its infusion, using a semiconductor laser device “UPL PDT”, with a wavelength λ=665±5 nm. The laser radiation dose density varied from 25 to 100 J/cm², the power density from 0.07 to 0.32 W/cm², the duration of one irradiation field - from 2 to 13.5 minutes, depending on its linear dimensions. The severity of adverse reactions was assessed on days 1-30 after treatment using the CTCAE 4.03 scale. The immediate results of treatment were assessed up to 3 months after PDT, with morphological confirmation of the response to treatment. No serious adverse reactions were observed during PS infusion and irradiation. No symptoms of dermal phototoxicity were reported. During control examinations, up to 3 months after irradiation in patients with flat and verrucous forms, the frequency of complete regressions was 97.1% (n=205) and 58.3% (n=6) cases, partial regressions - 2,9% (n=7) and 25% (n=3) of cases, respectively. Objective response rates were observed at 100% and 83.3%, respectively. The period of observation of patients varies from 3 to 120 months. (average 66 months). The frequency of disease relapses during this period was 9%. Patients with partial regression and identified relapse were treated with repeated PDT sessions. PDT is a well-tolerated and effective treatment method for patients with leukoplakia of the oral mucosa, which has significant advantages over traditional methods of treating this precancerous pathology. These include minimal toxicity to the normal tissues surrounding the pathological foci due to the selective accumulation of PS in leukoplakia tissues, a slight risk of serious adverse reactions, the possibility of an outpatient session, the possibility of repeated treatment over a large area of damage and good cosmetic results).